Design and Analysis of Tri Core Permanent Magnet Linear Generator for Wave Energy Conversion in South Coast of Java Island - sugita, Muhammad Rifa’i Putra; Wijaya, Fransisco Danang; Sarjiya, Sarjiya (2016)
The south coast of Java Island has significant wave height that allows for wave energy to electric energy conversion. Wave energy converter using permanent magnet linear generator (PMLG) attracting more attention due to its efficiency of the generator and the elimination of translational to rotational motion converter in the generator, but PMLG suffer from electric power losses in the winding. In this paper, a tri core PMLG design which has minimum electric power losses is proposed. The electric power losses in the winding are ideally minimized using simulated annealing algorithm. Then, finite element analysis is used to analyze and verify the proposed design of PMLG. The small scale optimum design of this PMLG is simulated using an oscillating water column (OWC) chamber to analyze and investigate the performance of this linear generator. Simulation result shows that PMLG has a good efficiency and confirm the capability of this PMLG installed with OWC chamber in the south coast of Java Island.